Variation and diversity of genus microcystis in the water environment of the Nui Coc reservoir, Thai Nguyen province - Thuỷ, Dương Thị; Phương Quỳnh, Lê Thị (Vietnam Journal of Biotechnology, 2018)
The Nui Coc reservoir, Thai Nguyen province was built on the Cong River for multi-purposes of providing water for local people such as agricultural irrigation, aquaculture, tourism activities and especially the drinking water supply for the Thai Nguyen city and other surrounding areas. This paper presents the results of the monthly surveys which were conducted during the year 2011 for determination of diversity of Microcytis and the microcystin contents in the isolated Microcystis strains in the water environment of the Nui Coc reservoir. The present results showed that eight species of Microcytis genus of which Microcystis aeruginosa in the water environment of the Nui Coc reservoir was the most abudance. The Microcystis cell density of the Nui Coc reservoir varied seasonally and the highest values were observed in high temperature in the rainy season. The results from the High-Performance Liquid Chromatography (HPLC) analysis showed that the microcystin contents in the isolated Microcystis strains from the Nui Coc reservoir ranged from 0.116 to 0.40 µg MC/mg dried mass. The high cell density of Microcystis and high microcystin concentrations in the isolated Microcystis strains from the Nui Coc reservoir revealed the potential risk for human health. The results also highlighted that it is very necessary and urgent to carry out regular monitoring programs for detecting the occurrence of cyanobacteria and phytoplankton in the water environment of the Nui Coc reservoir in order to timely warn the potential risk of cyanobacteria boom and the adverse impacts on the aquatic ecosystem and especially on human health.